2020
DOI: 10.1242/jeb.217091
|View full text |Cite
|
Sign up to set email alerts
|

Experimental support towards a metabolic proxy in fish using otolith carbon isotopes

Abstract: Metabolic rate underpins our understanding of how species survive, reproduce and interact with their environment, but can be difficult to measure in wild fish. Stable carbon isotopes (δ 13 C) in ear stones (otoliths) of fish may reflect lifetime metabolic signatures but experimental validation is required to advance our understanding of the relationship. To this end, we reared juvenile Australasian snapper (Chrysophrys auratus), an iconic fishery species, at different temperatures and used intermittent-flow re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 71 publications
(113 reference statements)
0
27
0
Order By: Relevance
“…To make the metabolic proxy comparable to conventional approaches used in measuring animal metabolism, the C resp values of the otoliths of Atlantic cod and Australasian snapper were successfully converted to metabolic rates expressed as oxygen consumption rates (Chung, Trueman, Godiksen, Holmstrup, et al., 2019; Martino et al., 2020). Our study did not record the oxygen consumption of cuttlefish; thus, temperature and body mass were fitted to a previously validated model (Melzner et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To make the metabolic proxy comparable to conventional approaches used in measuring animal metabolism, the C resp values of the otoliths of Atlantic cod and Australasian snapper were successfully converted to metabolic rates expressed as oxygen consumption rates (Chung, Trueman, Godiksen, Holmstrup, et al., 2019; Martino et al., 2020). Our study did not record the oxygen consumption of cuttlefish; thus, temperature and body mass were fitted to a previously validated model (Melzner et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Such approaches reveal an acute change in metabolic rates in a short period. Another novel metabolic proxy, namely the stable carbon isotope value (δ 13 C) recorded in biogenic carbonates, has been used to infer the averaged field metabolic rate of marine ectotherms within a time frame (Chung et al., 2019; Chung et al., 2019; Martino et al., 2020). This approach has been evaluated and applied to teleost fishes but not yet to cephalopods.…”
Section: Introductionmentioning
confidence: 99%
“…Both water temperature and δ 13 C in ambient water can partly influence the content of δ 13 C in the otolith [63,64]; however, the diet condition of the fish will continue to have the most important role [65,66]. Results indicated that the populations of C. nasus in the Yellow Sea and the Changjiang estuary were significantly greater than that in the Qiantang estuary.…”
Section: Discussionmentioning
confidence: 98%
“…Quantifying the impacts of urbanization on the field metabolic rate of freshwater fishes is difficult as a result of the significant lack of metabolic information for fish derived under field conditions (Treberg et al, 2016). However, the analysis of δ 13 C in fish otoliths has been shown to be representative of fish field metabolic rates (Chung M.-T. et al, 2019a;Martino et al, 2020) and is a promising tool for quantifying changes in metabolic rate in response to urbanization and environmental stressors. For example, Sinnatamby et al (2015) observed increases in otolith δ 13 C estimated field metabolic rates in young-of-year Arctic Charr as a function of increasing latitude, suggesting increased food consumption in high-latitude populations during the summer feeding period.…”
Section: Field Metabolic Ratesmentioning
confidence: 99%